Velázquez Soriano, I. y Espinosa Espinosa (eds.) (2021). Epigraphy in the Digital Age. Opportunities and Challenges in the Recording, Analysis and Dissemination of Inscriptions. Oxford: Archaeopress. ISBN: 978-1-7869-987-6, 240 págs - Herrera Rando, Javier (SPAL - Revista de Prehistoria y Arqueología, 2022)
Reseña del libro: Epigraphy in the Digital Age. Opportunities and Challenges in the Recording, Analysis and Dissemination of Inscriptions